Revisiting the dynamic relationship between exchange rates and stock prices in BRICS countries: a wavelet analysis - Dahir, Ahmed Mohamed; Mahat, Fauziah; Ab Razak, Nazrul Hisyam; Amin Noordin, Bany Ariffin (Borsa Istanbul Anonim Sirketi, 2018)
Based on a wavelet analysis, this study investigates the dynamic links between exchange rates and stock returns in Brazil, Russia, India, China, and South Africa (BRICS). The results reveal that relationships between exchange rates and stock returns are positive in the medium and long term, indicating that exchange rates lead stock returns in Brazil and Russia. However, the India index pair has a negative relation, and stock returns lead exchange rates in 64–128-day scales over the periods 2008, 2010–2012, and 2012–2015, while South Africa seems to have a more bidirectional causality; the Chinese index pair did not show any correlation. Further, the findings indicate that the crises had a substantial impact on links among the series. These results have important implications that investors should take into account in frequency-varying exchange rates and stock returns and regulators should consider to develop sound policy measures to prevent financial risk.